Stress and displacement intensity factors of cracks in anisotropic media - Kuznetsov, Sergey; Karakozova, Anastasia (Zielona Góra: Uniwersytet Zielonogórski)
A relation connecting stress intensity factors (SIF) with displacement intensity factors (DIF) at the crack front is derived by solving a pseudodifferential equation connecting stress and displacement discontinuity fields for a plane crack in an elastic anisotropic medium with arbitrary anisotropy. It is found that at a particular point on the crack front, the vector valued SIF is uniquely determined by the corresponding DIF evaluated at the same point.
Keywords: stress intensity factor; displacement intensity factor; anisotropy; asymptote; cracks; pseudodifferential equation